The Impact of Technological Investment and Sukuk Activities on Islamic Bank Performance: The Moderating Role of Sharia Governance - Qonitah Rifda Zahirah; Julina Julina; Slamet Haryono (JASF: Journal of Accounting and Strategic Finance, 2026)
Purpose: This study aims to examine the effect of technological investment components (ATM networks, software investment, and human resource expenses) and sukuk activities on the operational performance of Islamic banks in Indonesia. It addresses a gap in the literature by integrating these variables within a unified framework and by incorporating Sharia Governance as a moderating mechanism grounded in agency and stakeholder perspectives. The study also justifies the use of Return on Net Operating Assets (RNOA) as a profitability proxy that better captures operational efficiency in asset-based Islamic banking. Method: This study employs a quantitative approach using unbalanced panel data from 14 Islamic commercial banks in Indonesia over the period 2014–2024. The analysis applies Random Effects panel regression and Moderated Regression Analysis (MRA), while controlling for bank size and Financing to Deposit Ratio (FDR). Findings: The results show that ATM networks, human resource expenses, and sukuk activities positively and significantly affect RNOA, while software investment has no direct effect. Sharia Governance exhibits a differentiated moderating role: the Board of Directors strengthens the effect of ATM networks, the Audit Committee enhances the influence of human resource expenses, and the Sharia Supervisory Board reinforces the relationship between software investment and RNOA. Implications: These findings suggest that Islamic banks should balance physical and digital investments, strengthen human capital, and optimize sukuk utilization, while enhancing governance effectiveness to improve operational performance. Novelty/Value: This study contributes by integrating technological investment, sukuk activities, and multidimensional Sharia Governance within a single empirical framework, while introducing RNOA as a contextually relevant performance measure in Islamic banking.